Microstructure, Mechanical and Fractographic behaviour of the Diffusion Welded Joints of AA2219 and Ti-6Al-4V for aerospace applications - Manjunath Vatnalmath; V. Auradi; Bharath V Bharath; Anirudh Bharadwaj; Chetan Gowda; Madeva Nagaral (Fracture and Structural Integrity)
Diffusion welding is an advanced joining process that assures the feasibility of joining dissimilar metal alloys without producing metallurgical impurities at the joint interface. Two significant aerospace alloys, AA2219 and Ti-6Al-4V, are diffusion welded for the various holding times (30-120 minutes) by keeping the bonding temperature and pressure constant. The effect of holding time on the microstructure of the diffusion welded joints is evaluated using scanning electron microscopy (SEM), and the diffusion behaviour across the joint interface is ensued by the line scan energy dispersive spectroscopy (EDS). The obtained results show that the hardness across the joint interface is increased with increase in holding time. Furthermore, the maximum shear strength of 143.58 MPa is achieved for the joint formed at the holding time of 90 minutes and reduced thereafter. The formation of a thick intermetallic layer at a higher holding time strongly affects the shear strength. It is evident from the resulting fractured surfaces that the joints predominantly failed at the bonding interface, showcasing the brittle kind of failure. The X-ray diffraction (XRD) study on the fractured surfaces substantiates the formation of AlTi, Al2Ti and Al3Ti intermetallic compounds.